O efeito do exercício físico no número de unidades motoras em indivíduos afetados pela poliomielite - Simões, Jolanda Almeida Rosendo (2009)
The aim of this work was to evaluate the effects of the physical exercise on the number of motor units in the thenar muscles of individuals, sedentary and athletes, affected by poliomyelitis. In order to do this, the motor unit numbers were estimated by the electroneuromiographic technique of Motor Unit Number Estimation (MUNE), by recording the mean amplitude of surface motor unit potentials (SMUP) and the amplitude of compound muscular action potential (CMAP). Ten sedentary and eight athletes were evaluated in two sessions separated by six months. We estimated from literature the number of motor units for the thenar muscles of health individuals. To compare the MUNE between the two measures separated by six months and between the experimental groups we use two way ANOVA followed by the Bonferroni test. To compare the grouped values (first and second measures) of SMUP, CMAP and MUNE, between sedentaries and athletes, we used the non paired Student t test. To compare the MUNE values among health and polio individuals we used one way ANOVA followed by the Tukey multiple comparison test. We see no differences in the number of motor units between athletes and sedentaries (p=0.0726) or between the measurements done with six month intervals (p=0.9387); and there was no interaction among the two factors (p=0.5441). When the MUNE values were grouped, the t test did not show difference between sedentary and athletes (p= 0.0656). We noticed a clear decrease of MUNE values for the two polio groups when compared with the control group whosw data were taken from literature (saud x pólio sed: q0,05;2=16,49, p<0,001; saud x pólio atl: q0,05;2=16,37, p<0,001), but no difference between them (pólio sed x pólio atl: q0,05;2=0,7307 p>0,05). Our results suggest that physical exercise does not alter the number of motor units in polio affected individuals.